Screening and Optimization of Cellulase Production of Bacillus subtilis TD6 Isolated from Takifugu rubripes Fish - Andriani, Dian; Park, Don Hee (ANNALES BOGORIENSES, 2010)
Cellulase enzymes have attracted considerable attention in recent years due to their great biotechnological and industrial potential.  Cellulase enzymes provide a key opportunity for achieving tremendous benefits of biomass utilization through  the  bioconversion  of  the  most  abundant  cellulosic  material  into  the  simplest  carbohydrate monomer,  glucose.  Nowadays,  the  sources  of  cellulase-producing  bacteria  have  been  broadened  into  thepresence  of  symbiotic  bacteria  in  herbivorous  animal  and  also  from  marine.  Takifugu  rubripes  or  known  as puffer fish is a unique poisonous vertebrate  but nevertheless is considered a delicacy  in Korea. The diet of the puffer fish includes mostly algae. This dietary habit considers Puffer fish as host of cellulase-producing bacteria, especialy on its gut.  In the present study an attempt has been    made to search for the cellulolytic bacteria in the gut of Takifugu rubripes. Fifty five microorganisms have been isolated using 1% (w/v) Carboxymethyl cellulose (CMC) as substante Congo red  dye  test  and  DNS  method  were  then  used  for  screening  the  extracellular celuase activity of the strains. Among them, TD6 strain has shown the highest performance in term of cellulose activity. In order to evaluate the optimum culture condition of the isolate TD6 for cellulase production, the strain was grown at various temperatures, pH, carbon  sources, and  nitrogen sources.   Under optimum  condition, the maximum specific activity of 2.13 U/mg protein was achieved after growth the strain with 1.5% CMC at 45ºC PH 6 for 3 days, respectively Based on 16S rRNA gene analysis it is proposed that the strain was identified asBacillus subtilis.